Pemanfaatan Artificial Intelligence dalam Praktik Hukum: Peluang dan Tantangan Regulasi di Indonesia - Kristianti, Novera; Rolando, Bryand (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2025)
The development of Artificial Intelligence (AI) technology has brought significant transformation across various sectors, including the legal field. AI is increasingly utilized for automating legal research, analyzing contract documents, predicting case outcomes, and providing legal services through chatbots. While offering opportunities for increased efficiency and broader access to justice, the use of AI also presents serious challenges, particularly in terms of regulation and legal ethics. This study aims to examine the potential applications of AI in legal practice in Indonesia and to identify regulatory challenges arising from its use. The research employs a normative legal method with conceptual and comparative approaches, analyzing current regulations and practices in other jurisdictions such as the European Union and the United States. The findings indicate that Indonesia lacks a comprehensive legal framework to govern the use of AI in the legal sector, which poses risks related to accountability, algorithmic bias, and violations of privacy and professional ethics. Therefore, specific regulatory frameworks are urgently needed to ensure transparency, fairness, and accountability in the implementation of AI in legal practices.